Kesadaran Hukum Konsumen Muslim Pembeli Ragi Di Pasar Wiradesa Kabupaten Pekalongan terhadap Regulasi Sertifikasi Halal - Manasikana, Arina; Khasanah, Karimatul; Rahmawati, Heny (el hisbah Journal of Islamic Economic Law, 2022)
Based on Law No. 33 of 2014 concerning Halal Product Guarantee, all food products in circulation must be halal certified. However, the yeast sold at the Wiradesa Market is not yet halal certified. Interestingly, yeast that has not been certified halal is still in great demand by Muslim consumers. This study aims to determine the legal awareness of Muslim consumers regarding product regulations that must be halal certified and to determine the factors that influence the level of legal awareness of consumers buying yeast in the Wiradesa market. This type of research is field research using a qualitative approach. The results of this study indicate that the legal awareness of Muslim consumers buying yeast in the Wiradesa market is low. Indicators of legal knowledge and understanding are not fulfilled due to public ignorance regarding regulations on halal product certification. The factors that influence the level of legal awareness of Muslim consumers who buy yeast at the Wiradesa Market are educational factors and economic factors.